Use Of Assistive Technology In Learning To Read For Autistic Students (Case Study at DeWitt Middle School, Ithaca, New York State) - Maringgar Hangesti Putri; Wiwik Widajati; Budiyanto Budiyanto (Universitas Negeri Malang, 2025)
This study aims to describe the planning, implementation, obstacles, and supporting factors in the use of assistive technology in reading instruction for students with autism at DeWitt Middle School, Ithaca, New York State. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. Data analysis utilised data condensation, data presentation, and conclusion drawing and verification. The results of the study indicate that the planning of assistive technology utilisation was carried out through Individualised Education Programme (IEP) team meetings, which were responsible for determining the assistive technology appropriate to the students' needs. The procurement process is carried out by the Associate Principal of Inclusion through a submission to the ICSD Technology Department, with a provision time of between five days and one month. In the implementation of learning, assistive technology is used in an integrated manner through various media, including low-tech (printed books, flashcards), medium-tech (speakers, headphones), and high-tech (Chromebooks, various reading applications, and AAC iPads). This technology supports the process of early reading, reading comprehension, and alternative communication for autistic students with verbal impairments. The main obstacles encountered include difficulties for students in focusing their attention, limited ability to operate certain applications, and technical constraints such as unstable audio connections. Factors supporting the successful implementation of assistive technology include support from the school and district (ICSD), collaboration between the IEP team and parents, teacher training, and the availability of assistive technology that suits the needs of each student. This study concluded that the use of assistive technology at DeWitt Middle School has been well planned, implemented, and supported, thereby improving the motivation, participation, and reading skills of autistic students.